Epigraphica Boeotica II : further studies on Boiotian inscriptions - Fossey, John M. (Classical Studies E-Books Online, Collection 2014, ISBN: 9789004262430., 2014)
In Epigraphica Boeotica II John Fossey continues to treat results of his nearly 50 years of research into the archaeology and inscriptions of Ancient Boiotia ( Epigraphica Boeotica I, Amsterdam, 1991). The first part of the volume discusses the relations between Boiotia and other parts of the Greek world as seen in acts of proxenia and agonistic victor lists. After a section on dedications both religious and civic, there follows a series of studies of ancient tombstones, many of them spolia used in more recent buildings, with prosopographic and onomastic commentary on the names contained in them. Discussion throughout features letter forms and one specific example of this is an epigramme by the Roman philhellene emperor Hadrianus. An unusual rupestral text concludes the volume.